On the equilibrium density of ions in raining clouds - Chikina, I.; Shikin, V. (Recent Contributions to Physics, 2015)
On e of the debatable issues in meteorology is the source of enhanced ion density in storm clouds. This source is obviously related in some way to the density of rain drops in the storm cloud. It is also clear that all charging phenomena should involve free protons which are the highest mobility ions in the problem. Discussed in the present paper is the approach providing a ﬁnite ion density in the system of rain drops. The corresponding model for the storm cloud can be referenced as a “proton semiconductor” by analogy with electronic crystal semiconductors where charge is carried by light particles, i.e. electrons and holes.